Globalisasi Ekonomi Dan Implikasinya Bagi Negara-Negara Berkembang : Telaah Pendekatan Ekonomi Islam - Akhmad Nur Zaroni (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2015)
Economic globalization is the increasing economic integration and interdependence of national, regional and local economies across the world through an intensification of cross-border movement of goods, services, technologies and capital. Globalization leads to freer trade between countries. This is one of its largest benefits to developing nations. Homegrown industries see trade barriers fall and have access to a much wider international market. While an influx of foreign companies and foreign capital creates a reduction in overall unemployment and poverty, it can also increase the wage gap between those who are educated and those who are not. Over the longer term, education levels will rise as the financial health of developing countries rise, but in the short term, some of the poor will become poorer. Not everyone will participate in an elevation of living standards. According to Islamic economics, economic globalization should be done using appropriate approaches so as not to cause a lot of problems that could potentially harm the countries that are developing. The approach used should be based on fairness and equality in human interaction, and a multidisciplinary approach that covers all aspects of human life, moral, intellectual, social, historical, demographic, and political.